RNA‐seq analysis of mitochondria‐related genes regulated by AMPK in the human trophoblast cell line BeWo - Bin Wu; Albert Gao; Bin He; Yun Chen; Xiangfeng Kong; Fayuan Wen; Haijun Gao (Animal Models and Experimental Medicine)
Abstract Background How AMP activated protein kinase (AMPK) signaling regulates mitochondrial functions and mitophagy in human trophoblast cells remains unclear. This study was designed to investigate potential players mediating the regulation of AMPK on mitochondrial functions and mitophagy by next generation RNA‐seq. Methods We compared ATP production in protein kinase AMP‐activated catalytic subunit alpha 1/2 (PRKAA1/2) knockdown (AKD) and control BeWo cells using the Seahorse real‐time ATP rate test, then analyzed gene expression profiling by RNA‐seq. Differentially expressed genes (DEG) were examined by Gene Ontology (GO) analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment. Then protein–protein interactions (PPI) among mitochondria related genes were further analyzed using Metascape and Ingenuity Pathway Analysis (IPA) software. Results Both mitochondrial and glycolytic ATP production in AKD cells were lower than in the control BeWo cells (CT), with a greater reduction of mitochondrial ATP production. A total of 1092 DEGs were identified, with 405 upregulated and 687 downregulated. GO analysis identified 60 genes associated with the term ‘mitochondrion’ in the cellular component domain. PPI analysis identified three clusters of mitochondria related genes, including aldo‐keto reductase family 1 member B10 and B15 (AKR1B10, AKR1B15), alanyl‐tRNA synthetase 1 (AARS1), mitochondrial ribosomal protein S6 (MRPS6), mitochondrial calcium uniporter dominant negative subunit beta (MCUB) and dihydrolipoamide branched chain transacylase E2 (DBT). Conclusions In summary, this study identified multiple mitochondria related genes regulated by AMPK in BeWo cells, and among them, three clusters of genes may potentially contribute to altered mitochondrial functions in response to reduced AMPK signaling.